2018
DOI: 10.1155/2018/9765174
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Impedance Changes at Different Phases of Cerebral Edema in Rats with Ischemic Brain Injury

Abstract: Cerebral edema contributes significantly to the morbidity and mortality associated with many common neurologic conditions. Clinically, a diagnostic tool that can be used to monitor cerebral edema in real-time and differentiate between different types of cerebral edema is urgently needed. Because there are differences in electrical impedance between normal cortical tissue and cerebral edema tissue, electrical impedance tomography (EIT) can potentially be used to detect cerebral edema. Accurate recording of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 13 publications
1
27
0
Order By: Relevance
“…In 2018, Neeraja et al reported that the penetration depth of the sensor is inadequate to compensate for the increased distance between the sensor and brain tissue, thereby resulting in inaccurately high values (>80%) [21]. A shortcoming of EIT is that the highly resistant skull has a natural electrical isolation that limits current penetration and restricts deep imaging of the brain [22]. The main magnetic field created by a detection system can easily penetrate the skull although resistance is very high.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, Neeraja et al reported that the penetration depth of the sensor is inadequate to compensate for the increased distance between the sensor and brain tissue, thereby resulting in inaccurately high values (>80%) [21]. A shortcoming of EIT is that the highly resistant skull has a natural electrical isolation that limits current penetration and restricts deep imaging of the brain [22]. The main magnetic field created by a detection system can easily penetrate the skull although resistance is very high.…”
Section: Discussionmentioning
confidence: 99%
“…The MIPS variation trend in the experimental group may be related to the occurrence of cytotoxic edema and vasogenic edema after cerebral ischemia. According to the measurement result of Song et al [27], the dielectric property presented a first increasing and then decreasing trend after focal cerebral ischemic injury in mice. As pointed out by Schafer et al [28], the impedance of skeletal muscle also first increased and then decreased due to ischemia.…”
Section: Discussionmentioning
confidence: 98%
“…As pointed out by Schafer et al [28], the impedance of skeletal muscle also first increased and then decreased due to ischemia. According to the pathological process analysis of cerebral ischemic stroke, cytotoxic edema and vasogenic edema after cerebral ischemia constituted a dynamic variation process, where they played a dominant role at the early and later stages, respectively [27,29].…”
Section: Discussionmentioning
confidence: 99%
“…But continuous TCD is still under improvement. Electrical Impedance Tomography (EIT) has been proposed as a possible method to detect cerebral injuries (Song et al, 2018). Yet EIT requires current injection through a series of electrodes precisely placing on the corresponding position on the head, not mention that the current is ''blocked'' by the high resistivity skull which in turns may reduce the detection precision (Yan et al, 2017).…”
Section: Introductionmentioning
confidence: 99%